2019
DOI: 10.1089/cyber.2019.0079
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Social Media Use and Symptoms of Anxiety and Depressed Mood Among Icelandic Adolescents

Abstract: Adolescent use of social media platforms such as Facebook, Instagram, and Snapchat has increased dramatically over the last decade and now pervades their everyday social lives. Active and passive social media use may impact emotional health differently, but little is known about whether and to what extent either type of social media use influences emotional distress among young people. We analyzed population survey data collected from Icelandic adolescents (N = 10,563) to document the prevalence of social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
218
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 253 publications
(239 citation statements)
references
References 75 publications
16
218
2
3
Order By: Relevance
“…In conclusion, although adolescent use of social media appears to confer some benefits (Anderson and Jiang, 2018;Seabrook et al, 2016;Thorisdottir et al, 2019), it is also a relatively new and prevalent factor in the lives of adolescents that our data show is positively related to increased levels of psychological distress, although the effects were weak to small.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…In conclusion, although adolescent use of social media appears to confer some benefits (Anderson and Jiang, 2018;Seabrook et al, 2016;Thorisdottir et al, 2019), it is also a relatively new and prevalent factor in the lives of adolescents that our data show is positively related to increased levels of psychological distress, although the effects were weak to small.…”
Section: Discussionmentioning
confidence: 47%
“…For example, one important distinction is whether youth use social media actively (chatting with friends and posting content) or passively (scrolling, looking at content from others). A recent cross-sectional study of Icelandic adolescents found that using social media passively was positively associated with symptoms of emotional distress, while active social media use did not relate to emotional distress (Thorisdottir et al, 2019). Until the mechanisms are better understood, a careful presentation of the narrative is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations